(w,c)-almost periodic type functions and applications - 5. M. T. Khalladi, M. Kostić, A. Rahmani, D. Velinov (My University, 2023)
In this paper, we introduce several various classes of (w, c)-almost periodic type functions and their Stepanov generalizations. We also consider the corresponding classes of (w, c)-almost periodic type functions depending on two variables and related composition principles. We provide several illustrative examples and applications to the abstract Volterra integro-differential equations in Banach spaces.
Keywords: generalized (w, c)-almost periodic functions, generalized (w,c)- uniformly recurrent functions, abstract Volterra integro-differential equations